Nanoconfinement of borohydrides in hollow carbon spheres: Melt infiltration versus solvent impregnation for enhanced hydrogen storage. (30th August 2019) - Lai, Qiwen; Yang, Yuwei; Aguey-Zinsou, Kondo-Francois
Abstract: Nanoconfinement of complex hydrides and in particular borohydrides has appeared as a powerful method to modify the hydrogen storage properties of hydrides. However, the improvements obtained strongly depend upon the synthetic method. Herein, we assessed the effectiveness of melt infiltration and solvent impregnation under the same experimental conditions and with a porous carbon, to enable an effective nanoconfinement of borohydrides and further release of hydrogen at low temperatures. Owing to the different wetting conditions of borohydrides at the carbon surface, solvent impregnation was found to lead to the lowest hydrogen desorption temperatures with a desorption temperature as low as 100 °C achieved for nanoconfined LiBH4 and Mg(BH4 )2 . In this case, some reversibility of the hydrogen release was also observed at 300 °C under 6 MPa. In contrast, melt infiltration led to higher hydrogen desorption temperatures (>300 °C) owing to the difficulty of better confining the molten hydrides within the carbon porosity and no hydrogen reversibility was observed. The improvements in the hydrogen storage properties of borohydrides is thus extremely sensitive to the synthetic conditions (e.g. temperature) and this point toward the need of better approaches to enable the control of the properties of complex hydrides at the nanoscale. Graphical abstract: Image 1 Highlights: A range of borohydrides were confined in hollow carbons by melt infiltration and solvent impregnation. In most cases, solvent impregnation revealed to be more effective in leading to a low temperature release of hydrogen. Achieving good hydrogen properties for borohydrides strongly depend upon the synthetic approach.